Co-production of climate services: challenges and enablers - Jacob, Daniela; Lera St. Clair, Asun; Mahon, Roché; Marsland, Simon; Ndebele Murisa, Mzime; Buontempo, Carlo; Pulwarty, Roger S.; Siddiqui, Md Rezwan; Grossi, Amanda; Steynor, Anna; Mugandani, Raymond; Alexander, Lisa V.; et al. (Frontiers in Climate, 2025)
Climate change is often connected to an increase in weather extreme frequencies and severity, demanding an increased necessity in mitigating greenhouse gas emissions, adapting to and building resilience to these changes and impacts. This happens in a background of climate variability that already impacts several climate-sensitive sectors. There is an urgent need for fit-for-purpose climate services and service professionals to support these mitigation and adaptation efforts. Co-development of climate services can enhance their usefulness (context-specific and fit for purpose), usability (easy access and handling), and usage (transfer and upscale) by ensuring appropriate and iterative engagement between climate service providers and users, development of timely, reliable and usable products, and the provision of services to users in a truly accessible manner. Achieving co-development asks for reframing and scaled-up transdisciplinary, sustained, and multidirectional approaches between a diversity of information users and providers. For these processes, it is key to also address and further minimize or overcome barriers of co-production, while supporting enabling and accelerating mechanisms, better preparation of climate services providers including National Meteorological and Hydrological Services, private actors, civil society, and academia for interdisciplinary and transdisciplinary work, enhanced individual and institutional capacity development and governance mechanisms.